2017
DOI: 10.1155/2017/6796412
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Drug Delivery from pH- and Thermoresponsive Poly(N-Isopropylacrylamide)/Chitosan Core/Shell Nanocomposites Made by Semicontinuous Heterophase Polymerization

Abstract: Temperature- and pH-responsive core/shell nanoparticles were prepared by semicontinuous heterophase polymerization of N-isopropylacrylamide (NIPA) in the presence of chitosan micelles for drug delivery purposes. Micelles of chitosan, formed in an acetic acid aqueous solution at 70°C containing potassium persulfate, were fed with N-isopropylacrylamide (NIPA) at a controlled rate, to produce PNIPA/chitosan core/shell nanoparticles of about 350 nm. Then, the crosslinking agent, glutaraldehyde, was added to crossl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Huang et al obtained pH- and temperature-sensitive PNIPA/CS core/shell nanoparticles by emulsion polymerization with a T VPT of 33.4 °C [ 25 ]. Alvarado et al reported the synthesis of PNIPA/CS core/shell nanoparticles by semi-continuous heterophase polymerization (SHP) with a T VPT of 34 °C [ 26 ]. However, the T VPT of these nanoparticles is lower than the temperatures in the human body in response to infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Huang et al obtained pH- and temperature-sensitive PNIPA/CS core/shell nanoparticles by emulsion polymerization with a T VPT of 33.4 °C [ 25 ]. Alvarado et al reported the synthesis of PNIPA/CS core/shell nanoparticles by semi-continuous heterophase polymerization (SHP) with a T VPT of 34 °C [ 26 ]. However, the T VPT of these nanoparticles is lower than the temperatures in the human body in response to infection.…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al reported a lower amount of drug released from NIPA/CS core/shell nanoparticles at alkaline pH than at acidic pH [ 23 ]. Alvarado et al on the release of doxycycline hyclate from NIPA/CS core/shell nanocomposites also reported that at alkaline pH, the amount released was much lower than at acidic pH [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation